Capital humano: alocações de talentos do ensino superior no Brasil e seus possíveis impactos no crescimento econômico - Shirozono, Luanna Vargas (Universidade Federal de São Carlos, 2014)
Starting from the concept of human capital and considering it as a synonymous of knowledge, the present thesis collected based on lecture of Human Capital, searching in data of Higher Education in Brazil and studying a part of this topic and the effects over the dynamic of talents in the country. Searching inferences on alternative models of education from China, South Korea and The United States of America. Using as fundamental the HHJK theoretical model, the research concluded that to the period between 2002 and 2012, the distribution and allocation of talents among the knowledge areas / careers from Brazil didn t show a remarkable convergence if compared with state of São Paulo, which is the reference state by representation and importance in the country. Beyond that, the effects of those discrepancies among the occupation can correspond until 95% wage deviation on representative careers.
Human capital: the allocation of talents in higher education in Brazil and possible impacts for economic growth
Keywords: capital humano; desenvolvimento econômico; ensino superior - aspectos econômicos; human capital; higher education; allocation of talento; research & development; economic growth; CIENCIAS SOCIAIS APLICADAS::ECONOMIA